(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
Human-wildlife conflicts, particularly those involving large predators like Panthera species (lions, leopards, and tigers), have become an increasing global public health concern in recent years, especially in Southeast Asia. These conflicts often result in serious injuries and fatalities within affected communities. While not uncommon, attacks by Panthera species can lead to devastating traumatic injuries due to the animals’ strength and powerful bites. In this specific case, a worker at Abheda Biological Park entered the tiger enclosure and was attacked, sustaining multiple injuries that led to his death. Upon examination, the victim had numerous puncture and laceration wounds to the neck and chest, with internal injuries affecting the neck, lungs, and cervical spine. Serious injuries from wild animal attacks, especially from tigers, are commonly characterized by deep tissue damage and lacerations due to the animal’s powerful jaws and sharp teeth. This case report aims to highlight the specific injury patterns associated with tiger attacks, offering critical insights for healthcare providers. By understanding these patterns, medical professionals can be better equipped to treat the severe and often unique injuries resulting from such encounters in the future.